OPTIMALISASI STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN DAYA SAING UMKM DI ERA EKONOMI DIGITAL DI BARLINGMASCAKEB - Pratiwi, Agustin Riyan; Sumaya, Pupu Sriwulan (ICON Publisher, 2025)
This community service program aims to improve the understanding and skills of MSMEs in the Barlingmaskaceb area in implementing digital marketing strategies. Digitalization in marketing is an urgent need for MSMEs to be able to compete in the increasingly competitive era of industry 4.0. This program includes training and mentoring that focuses on the use of social media, marketplaces, and marketing data analysis to increase the effectiveness of business strategies. Through counseling methods, workshops, and direct mentoring, participants gain insight and practical skills in optimizing their digital marketing. The results of the program show that participants experienced an increase in understanding in managing digital marketing content more effectively and strategically. More consistent use of social media, optimization of marketplace features, and the use of analytical data in evaluating marketing performance have helped MSMEs increase market reach and customer loyalty. In addition, collaboration between MSMEs in joint marketing strategies has also proven to be able to strengthen their competitiveness in the digital market. Continuous mentoring and the formation of a digital MSME community are key factors in ensuring the sustainability of the impact of this program. As a recommendation, there needs to be further support from the government and related institutions to provide access to advanced training, digital infrastructure, and policies that support the digital transformation of MSMEs. The sustainability of this program can also be strengthened through regular monitoring of the development of MSMEs after training to ensure effective and adaptive strategy implementation. With a sustainable approach, this program is expected to become a model that can be applied in other regions to accelerate the digital transformation of MSMEs more broadly.